Variation of the minimally invasive CDCR technique. (3rd March 2020) - Pharo, Austin; Chelnis, James; Goecks, Tara; DeAngelis, Kendra C.; Fowler, Brian; Fleming, J. Chris; Naugle, Thomas C.
ABSTRACT: Purpose : Traditional (tCDCR) and endoscopic conjunctivodacryocystorhinostomy (eCDCR) are challenging surgical techniques requiring general anesthesia, a facial incision, and a large osteotomy and mucosal flap. Minimally invasive CDCR (miCDCR) techniques eliminate the need for some of the steps in t/eCDCR. Introduced here is a variation of the miCDCR technique using a Naugle-Fleming knurled dilator (NKD) to create the osteotomy and instruments within a central line catheter kit to help easily place or replace a Jones' tube into position within a bony conduit. Methods : This IRB-approved retrospective chart review examined all patients who underwent this miCDCR technique performed by two oculoplastic surgeons at Hamilton Eye Institute at the University of Tennessee Health Sciences Center from 2014 to 2016. Inclusion criteria: need for CDCR (either primary or repeat). Exclusion criteria: loss to follow up prior to six months. Primary endpoints: operative time, incidence of tube migration and complications, and cessation of epiphora. Results : Sixteen patients (nine men, seven women) were reviewed, with three undergoing bilateral procedure, totaling 19 cases. Age range: 47.0 to 84.0 years, average of 66.6 years ( SD = 11.1 ). Ten patients had surgery under local/MAC augmented with IV sedation, and six had general anesthesia (38%). Average operative time was 17.4 min ( SD = 10.9 ). One patient (5%) required revision in the six-month immediate post-operative period because of tube migration. All patients had cessation of epiphora. Conclusions : This procedure can be done safely and quickly without general anesthesia, resulting in a satisfactorily lower rate of tube migration and cessation of epiphora rates.